1980 Het wonderlijke jaar van de Vlaamse film : Slachtvee - De proefkonijnen - De Witte van Sichem - Hellegat - Holthof, Mark; Ruyters, Marc (Berchem : Uitgeverij EPO, 1980)
Henderickx, Guido ; Conrad, Patrick ; De Hert, Robbe ; Le Bon, Patrick
boek